2022
DOI: 10.1111/papt.12398
|View full text |Cite
|
Sign up to set email alerts
|

Do emotion regulation strategies mediate the attachment–paranoia association? An experimental study of repeated attachment imagery priming and stress buffering

Abstract: Objectives Paranoia describes unfounded interpersonal threat beliefs. Secure attachment imagery attenuates paranoia, but limited research examines mechanisms of change and no studies examine how secure imagery may be implemented most effectively in clinical practice. In this study, we tested: (a) the causal impact of secure, anxious, and avoidant attachment imagery on paranoia and anxiety, (b) whether emotion regulation strategies mediate these relationships, and (c) whether secure imagery buffers against soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
1
6
1
Order By: Relevance
“…State paranoia reduced from pre‐ to post‐imagery in the secure imagery condition as predicted, though no change was seen in the disorganised condition. This is consistent with previous research showing that secure attachment priming reduces paranoia (Sood et al, 2021, 2022; Sood & Newman‐Taylor, 2020). In the current study, the effect was found in a sample highly predisposed to AHs who had not been selected for elevated levels of paranoia, indicating that the effect of attachment security priming on paranoia is replicable and robust.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…State paranoia reduced from pre‐ to post‐imagery in the secure imagery condition as predicted, though no change was seen in the disorganised condition. This is consistent with previous research showing that secure attachment priming reduces paranoia (Sood et al, 2021, 2022; Sood & Newman‐Taylor, 2020). In the current study, the effect was found in a sample highly predisposed to AHs who had not been selected for elevated levels of paranoia, indicating that the effect of attachment security priming on paranoia is replicable and robust.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, the increase in dissociation might be due to secure images provoking distress in people with trauma histories (akin to fear of compassion; Gilbert et al, 2011). However, this has not been seen in previous priming studies which have recruited participants with high non-clinical paranoia, in which secure attachment priming is consistently associated with increased felt security (Newman-Taylor et al, 2021;Sood et al, 2021Sood et al, , 2022. The current study is the first to examine secure attachment priming in people vulnerable to voice-hearing, and future priming studies should control for past trauma (and linked beliefs).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This pragmatic study has been the first to explore the feasibility of conducting a trial comparing the effects of attachment security priming within an IAPT setting. The lack of any differences between the arms with regard to symptom reduction runs contrary to evidence using clinical (Carnelley et al, 2018;McGuire et al, 2018) and community (Sood et al, 2021) samples, where repeatedly priming attachment security has been found to improve symptoms. There are three key differences that might account for the disparity.…”
Section: Discussioncontrasting
confidence: 93%
“…The findings from this study emphasize the possibility to target intervention on state attachment insecurity, which could lead to improved emotional experience and reduced paranoia. By identifying attachment‐related experience and needs together with contextual factors related to state attachment insecurity fluctuation, it would be possible to focus on the key problem areas and develop specific ER strategies and reorganize maladaptive interpersonal patterns and beliefs (Mallinckrodt et al, 2009; Newman‐Taylor et al, 2021; Sood et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%